Theory and method in higher education research. - Huisman, Jeroen; Tight, Malcolm (International perspectives on higher education research ;, 2014)
Higher education research is a developing field internationally, attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies are being applied. As an expanding multidisciplinary area of interest, we may also expect increased development of theory and method.This is the second volume in this series dedicated to Theory and Method in Higher Education Research. Publishing contemporary contributions to international debates regarding the application and development of theory and methodology in researching higher education, this volume aims to offer a channel for discussion, critique and innovation. It should become essential reading for the growing numbers of researchers engaging with higher education across the globe.